Role of Melatonin in Timekeeping of Birds - Kumar, Vinod (Journal of Endocrinology and Reproduction, 2006)
The pineal is a component of the avian timekeeping system. The best known output of the pineal gland is melatonin, a lipophilic molecule, whose presence appears to have been evolutionarily conserved. Two major physiological roles are assigned to melatonin. One role is its involvement in daily and seasonal timekeeping. The other is its involvement in the time measurement. Birds use daily rhythm of melatonin secretion to decode the time-of-day as well as the time-of-year information. Besides these two roles, the other physiological roles that melatonin performs include immune function, free radical scavenging, etc. Interestingly, in birds the pineal (melatonin) directly regulates several circadian behaviours, but not the circadian rhythm mediated photoperiodic inductions; melatonin acts only as an endocrine modulator of the latter. In the present article the avian timekeeping system is very briefly described, and then the role of melatonin (and the pineal gland) in daily and seasonal timekeeping of birds is discussed.